1993
DOI: 10.1002/hep.1840180614
|View full text |Cite
|
Sign up to set email alerts
|

The role of transjugular liver biopsy in fulminant liver failure: Relation to other prognostic indicators

Abstract: Early and accurate diagnosis and prognosis of patients with fulminant liver failure is of critical importance for optimum management. We investigated the role of transjugular liver biopsy in the management of patients with fulminant liver failure and assessed its value in comparison with the recently proposed King's College criteria. Sixty-one patients with fulminant liver failure, ages 2 to 82 yr, were retrospectively analyzed. The main outcome measures were survival vs. death or progression to orthotopic liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(60 citation statements)
references
References 16 publications
8
49
0
1
Order By: Relevance
“…Studies addressing the prognostic value of liver biopsies with substantial necrosis are rare, and the conclusions are not well defined in the literature[14,15]. Hanau and colleagues questioned the value of hepatic necrosis in predicting clinical outcome, because about 50% of the biopsies in their study showed minimal bridging necrosis[7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies addressing the prognostic value of liver biopsies with substantial necrosis are rare, and the conclusions are not well defined in the literature[14,15]. Hanau and colleagues questioned the value of hepatic necrosis in predicting clinical outcome, because about 50% of the biopsies in their study showed minimal bridging necrosis[7].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Hanau and colleagues found that only one of seven (14.3%) patients whose liver biopsy demonstrated ≥ 70% necrosis survived without transplantation, keeping in line with our finding. In another study in 1993, Donaldson and colleagues found that only 2 of 19 patients (10.5%) with > 70% necrosis survived without transplantation[14]. These findings indicate that the percentage of hepatic necrosis may be an important prognosticator for patient survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been suggested to be of diagnostic and prognostic value, assisting clinical decision-making and timing of LT[5,6], in our survey it was not generally considered a requirement in clinical practice and was performed only in a small minority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the risk of bleeding following routine procedures such as insertion of central venous catheters or paracentesis and even for more invasive procedures such as trans-jugular LBX is considered small[5,18]. In contrast, the risk of intracranial hemorrhage following ICP monitor insertion is a major cause of concern in ALF patients with an incidence of fatal hemorrhage ranging from 1%-5%[19,20].…”
Section: Discussionmentioning
confidence: 99%